Alkaloids as Natural NRF2 Inhibitors: Chemoprevention and Cytotoxic Action in Cancer - Darinka Gjorgieva Ackova; Viktorija Maksimova; Katarina Smilkov; Brigitta Buttari; Marzia Arese; Luciano Saso (MDPI AG, 2023)
Being a controller of cytoprotective actions, inflammation, and mitochondrial function through participating in the regulation of multiple genes in response to stress-inducing endogenous or exogenous stressors, the transcription factor Nuclear Factor Erythroid 2-Related Factor 2 (NRF2) is considered the main cellular defense mechanism to maintain redox balance at cellular and tissue level. While a transient activation of NRF2 protects normal cells under oxidative stress, the hyperactivation of NRF2 in cancer cells may help them to survive and to adapt under oxidative stress. This can be detrimental and related to cancer progression and chemotherapy resistance. Therefore, inhibition of NRF2 activity may be an effective approach for sensitizing cancer cells to anticancer therapy. In this review, we examine alkaloids as NRF2 inhibitors from natural origin, their effects on cancer therapy, and/or as sensitizers of cancer cells to anticancer chemotherapeutics, and their potential clinical applications. Alkaloids, as inhibitor of the NRF2/KEAP1 signaling pathway, can have direct (berberine, evodiamine, and diterpenic aconitine types of alkaloids) or indirect (trigonelline) therapeutic/preventive effects. The network linking alkaloid action with oxidative stress and NRF2 modulation may result in an increased NRF2 synthesis, nuclear translocation, as well in a downstream impact on the synthesis of endogenous antioxidants, effects strongly presumed to be the mechanism of action of alkaloids in inducing cancer cell death or promoting sensitivity of cancer cells to chemotherapeutic agents. In this regard, the identification of additional alkaloids targeting the NRF2 pathway is desirable and the information arising from clinical trials will reveal the potential of these compounds as a promising target for anticancer therapy.